2017
DOI: 10.1093/aje/kww212
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Vitamin B12 Concentration in Pregnancy With the Risks of Preterm Birth and Low Birth Weight: A Systematic Review and Meta-Analysis of Individual Participant Data

Abstract: Vitamin B12 (hereafter referred to as B12) deficiency in pregnancy is prevalent and has been associated with both lower birth weight (birth weight <2,500 g) and preterm birth (length of gestation <37 weeks). Nevertheless, current evidence is contradictory. We performed a systematic review and a meta-analysis of individual participant data to evaluate the associations of maternal serum or plasma B12 concentrations in pregnancy with offspring birth weight and length of gestation. Twenty-two eligible studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
131
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 55 publications
0
131
2
8
Order By: Relevance
“…The effects of maternal B12 level on birth weight is still controversial, our results showed that the mean maternal vitamin B12 level in mothers with LBW [38] reviewed 29 articles and they concluded that although there is an association between low maternal vitamin B12 and intrauterine growth retardation, but no studies have definitively determined the cut off value for serum vitamin B12 level during pregnancy. Recently, a meta-analysis was done included eighteen studies observed no linear association between maternal B12 levels in pregnancy and birth weight, but B12 deficiency (<148 pmol/L) was associated with a higher risk of LBW in newborns (adjusted risk ratio = 1.15, 95% confidence interval (CI): 1.01, 1.31) [39]. However, several studies did not detect any association between maternal vitamin B12 levels and fetal growth restriction [3] [42].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of maternal B12 level on birth weight is still controversial, our results showed that the mean maternal vitamin B12 level in mothers with LBW [38] reviewed 29 articles and they concluded that although there is an association between low maternal vitamin B12 and intrauterine growth retardation, but no studies have definitively determined the cut off value for serum vitamin B12 level during pregnancy. Recently, a meta-analysis was done included eighteen studies observed no linear association between maternal B12 levels in pregnancy and birth weight, but B12 deficiency (<148 pmol/L) was associated with a higher risk of LBW in newborns (adjusted risk ratio = 1.15, 95% confidence interval (CI): 1.01, 1.31) [39]. However, several studies did not detect any association between maternal vitamin B12 levels and fetal growth restriction [3] [42].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between sociodemographic characteristics and early delivery may be explained by lifestyle and environmental determinants [49], including maternal body mass index [50], diet and micronutrient intake [51,52], physical activity [53], stress [54], employment conditions [55], active and passive smoking [49], and exposure to environmental pollutants [56]. Most of the research on the social and behavioral determinants of early delivery has focused on preterm birth; however, some studies find similar associations for early term births.…”
Section: Population Determinants: Socio-demographic Lifestyle and Enmentioning
confidence: 99%
“…Similar to the other studies, the relationship between B12 and LBW was not found in our current work. However, a recent meta‐analysis observed B12 deficiency (<148 pmol/L) to be associated with increased risk of LBW infants with an adjusted risk ratio 1.15 …”
Section: Discussionmentioning
confidence: 99%